Determination of N-acylhomoserine lactones from spoilage bacteria and aquatic product by integrative coupling method of solvent-terminated dispersive liquid-liquid microextraction and micellar electrokinetic capillary chromatography - Yue, Mei-E; Yu, Kaili; Lin, Qiaoyan; Xu, Jie; Jiang, Ting-Fu (Microchemical journal, 2019)
Microbial spoilage was the primary cause of food deterioration and caused huge economic losses and serious public health problems. The discovery of quorum sensing (QS) system got a new research orientation for the control of food spoilage. A fast, simple, and efficient method of solvent-terminated dispersive liquid-liquid microextraction (ST-DLLME) combined with micellar electrokinetic capillary chromatography was developed for the determination of N-acylhomoserine lactones from spoilage bacteria and aquatic product. In the procedure, the emulsion was formed by rapidly injecting a mixture of extraction solvent (carbon tetrachloride) and dispersive solvent (acetonitrile) rapidly into the aqueous sample solution. The acetonitrile was quickly injected into the emulsion as demulsification solvent, then the emulsion turned clear and became two phases. The last, the lower layer (carbon tetrachloride) as sample was collected and analyzed by capillary electrophoresis. Important parameters affecting the extraction efficiency of ST-DLLME were investigated in detail. Under the optimized conditions, the proposed method provided low limits of detection (below 5 ng.mL−1), a good linearity range of 5–1000 ng. mL−1, and good repeatability of the extractions (RSDs below 5.8%, n = 6). This proposed method was utilized to analyze the free extract of Pseudomonas aeruginosa CV12472, Aeromonas hydrophila PA01, fish and shrimp and obtained satisfactory results. The results indicated that the proposed method was successfully applied to the extraction of the routine analysis in the food field. •Solvent-terminated dispersive liquid-liquid microextraction was developed for detection of N-acylhomoserine lactones.•The emulsion was formed by rapidly injecting a mixture of carbon tetrachloride and acetonitrile.•The acetonitrile was used as demulsification solvent without using centrifugation.•Dispersive liquid-liquid microextraction combined with capillary electrophoresis.